2013
DOI: 10.1097/igc.0b013e3182981bdc
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Human Papillomavirus Infection and Activation of PI3K-AKT Pathway in Cervical Clear Cell Carcinoma

Abstract: Patients with stage I CCCC demonstrated good overall survival and rare recurrence. Clear cell carcinoma of the cervix is unrelated to high-risk HPV infection; hence, current vaccines will not prevent the incidence of CCCC. However, increased EGFR or HER2 expression or activation of AKT or mTOR was observed in all cases, indicating that inhibitors of tyrosine kinases or the AKT-mTOR pathway may be suitable treatment regimens for CCCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 30 publications
3
39
0
1
Order By: Relevance
“…mTOR signaling pathway inhibitors might be a new therapeutic treatment in cervical cancer, 28 and SPAG5 expression in cervical cancer may be a potential indicator for mTOR inhibitor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…mTOR signaling pathway inhibitors might be a new therapeutic treatment in cervical cancer, 28 and SPAG5 expression in cervical cancer may be a potential indicator for mTOR inhibitor treatment.…”
Section: Discussionmentioning
confidence: 99%
“…One study examining various molecular pathways by immunohistochemistry showed that a proportion of cervical CCCs had loss of PTEN, positivity for pAKT, and positivity for pmammalian target of rapamycin (mTOR) with 1 case showing human epidermal growth factor receptor 2 (HER2) amplification by fluorescence in situ hybridization. 67 However, no molecular analysis was performed in these cases and therefore, the correlation of these results with actual mutations is unknown.…”
Section: Clear Cell Carcinomamentioning
confidence: 98%
“…Adenocarcinomas (including adenosquamous carcinomas) are the second most common histologic type linked to HPV infection, specifically usual-type endocervical, mucinous intestinal and villoglandular subtypes, followed by high-grade neuroendocrine carcinomas (HGNEC). Non-HPV-associated cervical carcinomas are rare, and predominantly comprise unusual adenocarcinoma variants: mesonephric adenocarcinoma, minimal deviation/gastric-type mucinous adenocarcinoma, and clear cell carcinoma (2, 3). …”
Section: Introductionmentioning
confidence: 99%